2018
DOI: 10.1007/s11614-018-0301-2
|View full text |Cite
|
Sign up to set email alerts
|

Europäische Solidarität in Zeiten der Krise: ein Vergleich der transnationalen Aktivitäten zivilgesellschaftlicher Organisationen in Deutschland und Griechenland

Abstract: Civil society organisations have been engaged in solidarity practices in various issue areas, both within their countries and beyond. This paper is interested in analysing whether and to what extent civic initiatives and organisations are involved in transnational solidarity activities within Europe. Moreover, it wishes to identify those factors that seem to promote or inhibit the scope of transnational European activities. The paper compares the situation in two countries (Greece and Germany) on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Based on our examination, we find ( Figure 3.1) that overall NGOs are the most frequent actor, as seen in almost half (46.3%) of all TSOs. This is a non-surprising finding as similar studies have shown that European civil society is dominated by formal humanitarian organisations such as NGOs (Warleigh, 2001;Lahusen et al, 2018). Other expected significant solidarity providers are the Church and charities as well as social economy enterprises and unions (18.4% and 17.0%, respectively).…”
Section: Who Are the Innovating Tsos? Types Starting Year And Actionsmentioning
confidence: 71%
See 2 more Smart Citations
“…Based on our examination, we find ( Figure 3.1) that overall NGOs are the most frequent actor, as seen in almost half (46.3%) of all TSOs. This is a non-surprising finding as similar studies have shown that European civil society is dominated by formal humanitarian organisations such as NGOs (Warleigh, 2001;Lahusen et al, 2018). Other expected significant solidarity providers are the Church and charities as well as social economy enterprises and unions (18.4% and 17.0%, respectively).…”
Section: Who Are the Innovating Tsos? Types Starting Year And Actionsmentioning
confidence: 71%
“…Thus, previous research has shown that centralised and formally structured organisations mobilise resources and achieve goals more effectively than decentralised and informal groups (Jenkins, 1983;Edwards and McCarthy, 2004). Based on this approach, as similar studies have shown (Lahusen et al, 2018;Loukakis and Maggini, 2018) we can expect that European solidarity is strongly affected by the structure and resources of the organisations we have coded, regardless of their field of activity. Therefore, our first hypothesis is as follows:…”
Section: Applying Existing Knowledge To Tsos: Explanatory Factors Andmentioning
confidence: 91%
See 1 more Smart Citation
“…However, as discussed in this book (e.g. Chapter 8), we have found evidence of horizontal transnationalisation (Lahusen et al, 2018) among the more grass roots-based and informal models of collective action and civil society. Civil society-led transnational solidarity comes at a time when reactionary parties and xenophobic movements are on the rise in Europe and beyond, and therefore our findings act as a signal that efforts to construct a truly transnational civil society may be more necessary than they have been before.…”
Section: Resultsmentioning
confidence: 51%
“…Research findings on the scope of activities suggest that despite tensions between the international and the local scopes of action, the everyday practices of cooperation remain tied to the local level (Anheier and Themudo 2002;von Bülow 2010;Baglioni and Giugni 2014). Even the organizations engaged in transnational solidarity remain primarily active at the local or national level (Lahusen et al 2018). Moreover, the dichotomy between 'professionalized' and 'spontaneous' organizations does not only generate competition for resources but also cooperation between large and small organizations (Kriesi 2007).…”
Section: The Forms Of Organisations In the Field Of Csosmentioning
confidence: 99%